Chronic kidney disease biomarkers and mortality among older adults: A comparison study of survey samples in China and the United States. - Hui Miao; Linxin Liu; Yeli Wang; Yucheng Wang; Qile He; Tazeen Hasan Jafar; Shenglan Tang; Yi Zeng; John S Ji (PLoS ONE, 2022)
Objectives Among older adults in China and the US, we aimed to compare the biomarkers of chronic-kidney-diseases (CKD), factors associated with CKD, and the correlation between CKD and mortality. Setting China and the US. Study design Cross-sectional and prospective cohorts. Participants We included 2019 participants aged 65 and above from the Chinese Longitudinal Healthy Longevity Study (CLHLS) in 2012, and 2177 from US National Health and Nutrition Examination Survey (NHANES) in 2011-2014. Outcomes Urinary albumin, urinary creatinine, albumin creatinine ratio (ACR), serum creatinine, blood urea nitrogen, plasma albumin, uric acid, and estimated glomerular filtration rate (eGFR). CKD (ACR ≥ 30 mg/g or eGFR< 60 ml/min/1.73m2) and mortality. Analytical approach Logistic regression and Cox proportional hazard models. Covariates included age, sex, race, education, income, marital status, health condition, smoking and drinking status, physical activity and body mass index. Results Chinese participants had lower levels of urinary albumin, ACR, and uric acid than the US (mean: 25.0 vs 76.4 mg/L, 41.7 vs 85.0 mg/g, 292.9 vs 341.3 μmol/L). In the fully-adjusted model, CKD was associated with the risk of mortality only in the US group (hazard ratio [HR], 95% CI: 2.179, 1.561-3.041 in NHANES, 1.091, 0.940-1.266 in CLHLS). Compared to eGFR≥90, eGFR ranged 30-44 ml/min/1.73m2 was only associated with mortality in the US population (HR, 95% CI: 2.249, 1.141-4.430), but not in the Chinese population (HR, 95% CI: 1.408, 0.884-2.241). Conclusions The elderly participants in the US sample had worse CKD-related biomarker levels than in China sample, and the association between CKD and mortality was also stronger among the US older adults. This may be due to the biological differences, or co-morbid conditions.